Oxidative Stress and ROS Link Diabetes and Cancer - Homer S. Black (MDPI AG, 2024)
Type 2 diabetes mellitus (T2DM) accounts for one-sixth of deaths globally, whereas cancer is the second leading cause of death in the U.S. T2DM is a known risk factor for many cancers. Reactive oxygen species (ROS)-altered metabolic and signaling pathways link T2DM to cancer. These reprogrammed metabolic and signaling pathways contribute to diabetic complications, impact the redox balance (oxidative stress), and have differential roles in the early and late stages of cancer. A respiratory chain that is highly reduced (as under hyperglycemic conditions) or if reduced cofactors accumulate, ROS are greatly elevated. ROS may cause mutations in mitochondrial DNA (mtDNA) that result in further ROS elevations. The amplification of ROS results in the activation of PKC, an overarching signaling pathway that activates MAPK with a subsequent regulation in several factors that result in pathophysiological manifestations of T2DM and cancer. An upregulation in PKC leads to a deregulation in NF-kß, which regulates the PKB/P13/Akt pathway and orchestrates the cell survival, growth, proliferation, and glucose metabolism manifested in cancer. It also affects Insulin Receptor Substrate (IRS-1), decreasing insulin-stimulated glucose transport and glucose uptake, disrupting subsequent cell signaling pathways contributing to the development of T2DM. Dyslipidemia is a hallmark of T2DM and cancer. ROS-induced lipid peroxidation leads to systemic inflammation, producing inflammatory prostaglandins, cytokines, and chemokines that result in tumor proliferation, rapid tumor growth, and modulation of immunity. The dual role of ROS in the early and late stages of cancer makes antioxidant therapy precarious and may be responsible for controversial results. A system that delivers an antioxidant directly to mitochondria may be useful in inhibiting the formation of ROS early during the pre-diabetic stage, whereas antioxidant therapy must be halted in later stages to retard metastasis.